Så kommer det et lite pling … Internett og sosiale mediers betydning for eldres hverdagsliv [Then there's a little pling ... The significance of the Internet and social media for older adult's everyday lives] - Lie, Malene Paulsen (MedieKultur: Journal of media and communication research, 2017)
Quantitative studies show that older adults are the main consumers of traditional mass media, but also that their use of the Internet and social media increases every year. Despite these developments in the media usage of older adults, only a few studies have inquired into the ways in which older adults use the Internet and social media in everyday life. The current study is based on semi-structured, long interviews with older Internet users. The empirical material documents that usage of the Internet plays a significant role for the participants' experience of time and place. However, the descriptions of the everyday rhythm of media useage differs between those who use social media and those who do not. While the non-users adhere to a more linear "media rhythm" with fixed times of use, those who do use social media show a more dynamic and interactive everyday rhythm. For instance by being contineously drawn into new conversations and discussions by Facebook notifications. The study indicates that the use of Facebook, and the Internet in general, plays a transformative role for the everyday life of older adults and their relations with others.